FEATURES OF THE USE OF A BONE BLOCK TAKEN FROM THE ZONE OF THE ZYGOMATIC-ALVEOLAR BUTTRESS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Limited maxillary defects are commonly grafted with bone blocks harvested from the symphysis or the ramus; harvesting a second surgical site in the mandible increases both operative time and patient's postoperative morbidity. To overcome these disadvantages, the zygomatic buttress (ZB) was suggested as an alternative maxillary source of autogenous bone. This intraoral donor site has a natural convex shape and can be accessed along with the recipient site through the same flap design. We report a case series describing this uncommon technique of bone harvesting from the zygomatic buttress to reconstruct limited alveolar defects in the maxilla.